Refining Pedagogical Skills in LS-Driven TP: Insights into PSCST’s Professional Competence - Sri Mulyani Sabang; Muhammad Fachri B. Paloloang; I Komang Werdhiana; Muh. Syarif S. Abd. Syukur; Dewi Satria Ahmar; Muhammad Fath Azzajjad (Jurnal Penelitian Pendidikan IPA, 2026)
This quantitative study examines the impact of a teaching practicum, integrated with Lesson Study, on the pedagogical competency of 93 pre-service science teachers in the Pendidikan Profesi Guru (PPG) program at Universitas Tadulako, Indonesia.  This study is a quantitative survey using purposive-stratified sampling (N = 93 PPG teachers). The data relied on self-assessment questionnaires, risking subjective bias. The intervention included iterative Lesson Study cycles (Plan–Do–See–Reflection). Practically, the results support LS-based practicum improvement, but generalization is limited to similar PPG contexts and regional settings. Data were gathered using self-assessment questionnaires and bolstered by Lesson Study, using a validated 5-point Likert-scale instrument that was aligned with the four phases of Lesson Study (Plan, Do, See, Reflection). The findings supported H₁ and rejected H₀, indicating a high level of general pedagogical competency (M = 3.62, SD = 0.45).  Plan (M = 3.67) and Do (M = 3.65) phases showed strengths, especially in ICT integration and conceptual clarity, while See (M = 3.55) and Reflection (M = 3.58) phases showed relative deficiencies.  Regression analysis revealed that Reflection ratings significantly predicted overall competency (β = 0.32, p < 0.001, R² = 0.28), and repeated-measures ANOVA validated significant phase differences (F (3,276) = 4.82, p = 0.003, η² = 0.05). The results demonstrate how well Lesson Study promotes evidence-based pedagogical development, particularly through iterative reflection, and provide empirical evidence in favor of its broader implementation in Indonesian PPG programs to improve science teacher training in areas with limited resources. This study contributes theoretically by operationalizing PSCST-based pedagogical competence within a Lesson Study framework.